2019
DOI: 10.3139/120.111396
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the boron layer formed by pack boronizing of binary iron-niobium alloys

Abstract: In this study, Fe-1Nb, Fe-5Nb and Fe-10Nb (at.-%) binary alloys were boronized by the pack boronizing method at 950 °C for 3 h. The effect on the boride layer of the increasing niobium amount in pure the iron was experimentally investigated. After boron treatment, microstructural changes occurring on the surfaces of the coated alloys were examined by SEM, EDS and XRD analysis. A microhardness test analysis was applied to the coated alloys. Typical saw tooth morphologies were present in all coated alloys. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The unborided Hardox 450 steel exhibited the highest wear rate. In contrast, the lowest wear rate occurred in the Hardox 450 samples borided at 900 ∘ C owing to toughness of the Fe 2 B and FeB phases, and also, the lowest wear rate for Hituf steels came about in the samples borided at 800 ∘ C. Due to the decrease in the hardness with the growth of crystals of borides formed at high boriding temperatures, there was an increase in wear rates in Hardox 450 borided at 1000 ∘ C as well as HiTuf steel borided at 900 and 1000 ∘ C. It was reported that the hardness and thickness of the boride layers formed on the surface [3,13,37] and also the other factors such as adhesion strength, elasticity modulus and fracture toughness [38] might have a considerable effect on wear resistance, and the increase in hardness and thickness could ensure greater resistance to abrasive wear. According to the results of the wear test, it has been shown that the wear resistance of the borided samples significantly enhanced by the boriding treatment due to having high toughness of the Fe 2 B and FeB boride layers.…”
Section: Resultsmentioning
confidence: 99%
“…The unborided Hardox 450 steel exhibited the highest wear rate. In contrast, the lowest wear rate occurred in the Hardox 450 samples borided at 900 ∘ C owing to toughness of the Fe 2 B and FeB phases, and also, the lowest wear rate for Hituf steels came about in the samples borided at 800 ∘ C. Due to the decrease in the hardness with the growth of crystals of borides formed at high boriding temperatures, there was an increase in wear rates in Hardox 450 borided at 1000 ∘ C as well as HiTuf steel borided at 900 and 1000 ∘ C. It was reported that the hardness and thickness of the boride layers formed on the surface [3,13,37] and also the other factors such as adhesion strength, elasticity modulus and fracture toughness [38] might have a considerable effect on wear resistance, and the increase in hardness and thickness could ensure greater resistance to abrasive wear. According to the results of the wear test, it has been shown that the wear resistance of the borided samples significantly enhanced by the boriding treatment due to having high toughness of the Fe 2 B and FeB boride layers.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate selection of coating might increase the performance of AISI M2 mandrel and thereby increase the life. Transition metal carbides and nitrides were widely used in tribological applications for excellent corrosion and wear resistance, higher hardness and low co-efficient of friction [1]. PVD, CVD and thermo-reactive diffusion (TRD) are the different techniques used to form transition carbide and nitride coating [2,3].…”
Section: Introductionmentioning
confidence: 99%